Reducing the frequency of aspirating gastric tubes in patients enterally fed in the ICU: A randomised control trial - Williams, T.; Leslie, Gavin; Mills, L.; Davies, H.; Leen, T.; Dobb, G. (Elsevier Inc, 2013)
BACKGROUND: Enteral nutrition (EN) tolerance is monitored by aspirating stomach contents by syringe at prescribed intervals. No studies have been conducted to assess the most appropriate time interval for aspirating gastric tubes.AIM: To compare four-hourly gastric tube aspiration (usual care) to a variable regimen (up to 8-hourly aspirations).METHOD: This randomised control trial (RCT) enrolled patients who stayed in the ICU > 48 h, had a gastric tube, and were likely to receive EN for 3+ days. Patients were randomised (computer-generated randomisation) to either control group (4-hourly) or intervention group (variable regimen). The primary outcome was the number of gastric tube aspirations per number of feeding days from randomisation until EN was ceased or up to 2 weeks post-randomisation.RESULTS: Following Institutional Ethics Committee approval, 358 patients were recruited (control group n = 180 and intervention group n = 178). No differences were found in age, sex, worse Acute and Chronic Health Care Evaluation II score or time to commencement of EN. In the intention to treat analysis, the intervention group had fewer tube aspirations per feed time (0.21 versus 0.32 in the control group, p < 0.001). There were no differences in complications.CONCLUSION: This study is the first to use a RCT to examine the frequency of gastric tube aspirations. The frequency of gastric tube aspirations was reduced in the variable regimen group with no increase in risk to the patient. The reduced frequency of aspirations saves nursing time, decreases the risk of contamination of the EN circuit and minimises the risk of body fluid exposure.